The personal fonds of Chimit-Dorzhu Baiyrovich Ondar in the National Archives of the Republic of Tuva - Kotyusheva, Tatyana E.; Archimaeva, Alexandra I. (The New Research of Tuva, 2022)
The article presents an overview of the personal archive entitled “Chimit-Dorzhu Baiyrovich Ondar, a prominent statesman and public figure of Tuva and Russia. The Chairman of the Council of Ministers, Supreme Council of the Tuvan ASSR, People’s Deputy of the RSFSR (1990–1993), Deputy of the State Duma (2003–2007)” at the National Archives of the Republic of Tuva.Ch.-D. B. Ondar is one of the famous leaders of Tuva of the Soviet period who worked as Chairman of the Supreme Council of the Tuvan ASSR (until 1991). His name is associated with active construction, rapid development of Tuva after its entry into the USSR.The fonds contains 52 items for the period of 1958–2016. These are documents on official and public activities, biographical and creative materials as well as those collected by the holder of the archive. A special feature of the collection 914 is the fact that it contains several manuscripts written by the author himself. Some of them have already been published as books, the rest are still waiting for their time to come. The main milestones of Ch.-D. B. Ondar’s biography and the landmarks of his labor activity at a brewery, in the construction and mining industries, etc. were determined based on the documents.
Keywords: Chimit-Dorzhu Baiyrovich Ondar; archival document; personal fonds; National Archives of the Republic of Tuva; history of Tuva; Tuva